Pengaruh Pengembangan Karir Dan Motivasi Terhadap Kepuasan Kerja Pegawai Pada Dinas Perhubungan Kabupaten Pali (Jurnal Manajemen dan Investasi (MANIVESTASI), 2025)
ABSTRACT The aim of this research is to find out if it is affected by Career Development and Motivation on Job Satisfaction at the Department of Transportation of Pali Regency. The strategy used in this study is a quantitative technique with the number of tests concentrated on over 35 individuals. Information checking strategies used in this review are different recurrence investigations, recurrence coefficient investigations, assurance checks, t-tests and f-tests using the SPSS 22 for windows program. From the results of the t-test research, it shows that there is a significant influence on Career Development (X1) with a sig value of 0.000